Effect of vaccine dose on severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) antibody levels in a vaccinated community in Gowa Regency, Indonesia - Andi Magfirah Hamsi; Ridwan Amiruddin; A. Arsunan Arsin; Andi Zulkifli Abdullah; Hasnawati Amqam; Shanti Riskiyani (Journal of Education and Health Promotion, 2024)
BACKGROUND: The administration of the coronavirus disease 2019 (COVID-19) vaccine aims to stimulate the production of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) antibodies. This leads to an enhanced production of neutralizing antibodies (Nabs), which naturally neutralize the virus within the body, thereby reducing the risk of COVID-19 infection. This study determined the analysis of factors affecting SARS-CoV-2 antibody levels in vaccinated individuals using data from the COVID-19 Seroepidemiological Survey of Gowa Regency. METHODS AND MATERIAL: This was an analytic observational study with a cross-sectional design. The COVID-19 Seroepidemiology Survey data as a whole were 851 individuals, and in this study, the number of samples was 804 individuals from all COVID-19 Seroepidemiology Survey samples who had performed the COVID-19 vaccine in Gowa Regency, selected through purposive sampling. STATISTICAL ANALYSIS USED: Data analysis was conducted using various statistical tests, including the independent-samples t-test, Mann–Whitney test, Kruskal–Wallis test, and multiple logistic regression. Furthermore, the analysis was performed through the STATA program version 14.0. RESULTS: There was a significant influence between the history of COVID-19 infection (P = 0.0006) and dose of vaccine (P = 0.0001) with SARS-CoV-2 antibody levels in vaccinated individuals. Meanwhile, vitamin consumption and comorbid history did not affect SARS-CoV-2 antibody levels. Multivariate analysis showed that vaccine dose was the most influential variable on antibody levels (P = 0.046; Odds Ratio (OR) 0.19; 95% Confidence Interval (CI): 0.036–0.968). CONCLUSIONS: The most influential factor was the vaccine dose on SARS-CoV-2 antibody levels in community in Gowa Regency.